البطالة في الوطن العربي تحديد المشكلة والآثار وآليات الإنتاج و الحل - تركية, بهاء الدين (Latakia University Journal - Arts and Humanities Sciences Series, 2014)
مشكلة البطالة ظاهرة مركبة ذات أبعاد اجتماعية، واجتماعية، وأمنية، وسياسية اقتصادية، سياسية ، ديمغرافية، تؤثر وتتأثر ببقية الظواهر الاجتماعية وتعتبر مشكلة البطالة من Hخطر المشاكل التي تواجه المجتمع العربي والاقتصاد العربي والتي تواجه المجتمع الانساني وهذه الظاهرة تثقل عاتق المجتمع واقتصاده وهذه الظاهرة تتطلب وضع سياسات وحلول من أجل محاولة السيطرة على المعدلات المرتفعة للبطالة ,والبطالة هي مشكلة هيكلية تتركز في الفئات الشابة وبخاصة المتعلمة منها وتعد ضياعا وهدرا لطاقات المجتمع عامة والشباب بخاصة . تردي وضع البطالة على المستوى العالمي والعربي جاء نتيجة لتردي الأوضاع الاقتصادية والاجتماعية بمقارنة نسب البطالة بين مناطق العالم فان الوطن العربي يواجه اليوم أسوأ بطالة في العالم . Unemployment constitutes the most dangerous problem which faces the Arab economy, Unemployment is considered a huge waste of unemployed human society capabilities, which is a heavy burden the national economy and need to putting policies for finding solutions for this problem and limiting the increase of its averages and trying to reduce its rates that unemployment in. Arabcounrties. is a structural problem and concentrates in young people and those who have recently entered the labour market, especially educated groups suggests that the solution of the problem lies in enhancing the investment climate putting policies for finding solutions for this problem and limiting the increase of its averages and trying to reduce its rates